An Evaluation of "A Novel Approach to Reading" (an individualized reading program in Grade 7, Queen Mary Elementary School, Vancouver, for the 1970-71 school year) - Ellis, E. N.; Vancouver Board of School Trustees (British Columbia). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
An individualized reading program designed to improve pupils' attitudes toward reading is evaluated. A classroom was equipped with paperback novels chosen by the students, and an informal reading environment was provided. Reading skills lessons and remedial activities were administered when necessary. Test results indicated that pupils made significant gains in the abilities measured. Reactions of parents, an outside observer, and pupils were favorable. Appendices include reading test score distributions and a summary of pupil questionnaire responses. (MS)
Educational level discussed: Grade 7.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Grade 7.; Individualized Reading; Interests; Paperback Books; Parent Attitudes; Program Evaluation; Questionnaires; Reading Ability; Reading Rate; Student Attitudes; Gates MacGinitie Reading Tests